2007
DOI: 10.1259/bjr/99530445
|View full text |Cite
|
Sign up to set email alerts
|

Target cell frequency is a genetically determined risk factor in radiation leukaemogenesis

Abstract: Whole body exposure to ionizing radiation increases the risk of radiation-induced acute myeloid leukaemia (r-AML). r-AML is the result of the accumulation of mutations in a single haemopoietic stem cell, so risk is therefore a function of the number of mutations required to transform the stem cell and the mutation rate. There is a genetic component to the risk of AML within the general population, and low penetrance variant alleles encoding DNA repair enzymes have been genetically implicated in therapy-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Studies in mice 17,30 and humans 31,32 support the concept that susceptibility to myeloid leukemia has a genetic component. In addition, environmental factors (eg, genotoxic therapy) and geneby-environment interactions contribute to t-AML susceptibility.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies in mice 17,30 and humans 31,32 support the concept that susceptibility to myeloid leukemia has a genetic component. In addition, environmental factors (eg, genotoxic therapy) and geneby-environment interactions contribute to t-AML susceptibility.…”
Section: Discussionmentioning
confidence: 94%
“…Intermediate phenotypes relevant for t-AML include the response to DNA damage, the efficiency of drug metabolism, and/or the frequency of cells vulnerable to transformation. Correspondingly, QTLs influencing stem cell number 30 and genes involved in DNA repair and drug metabolism [12][13][14] have been associated with t-AML susceptibility. Human studies have identified a limited number of genetic variants that are more prevalent in affected persons, but because of the complex nature of t-AML susceptibility, it is likely that important genetic determinants have not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
“…(2001) is instructive; using a PCR-based molecular approach, these workers showed that the frequency of the radiation-induced ‘loss of heterozygosity’ (LOH) of chromosome 2 within stem cells of CBA/H × C57BL/6 F 1 mice was no greater than the induced LOH in other control chromosomal regions evaluated. (A69) So what are the rate limiting steps? It has been suggested that the absolute number of marrow stem cells defines the number of potential radiation-transformable genomes, and in turn, overall leukaemogenic risk (Jawad et al., 2007). If this is the case, then it is the number of available targets within the defined radiation volume that determines the leukaemic rate, and in turn, the efficiency of the irradiation.…”
Section: Annex a Haematopoietic Tissues: Role Played By Stem Cells Amentioning
confidence: 99%
“…(A69) So what are the rate limiting steps? It has been suggested that the absolute number of marrow stem cells defines the number of potential radiation-transformable genomes, and in turn, overall leukaemogenic risk (Jawad et al., 2007). If this is the case, then it is the number of available targets within the defined radiation volume that determines the leukaemic rate, and in turn, the efficiency of the irradiation.…”
Section: Annex a Haematopoietic Tissues: Role Played By Stem Cells Amentioning
confidence: 99%
“…Genetic loci that confer a susceptibility to spontaneous or induced haemopoietic malignancies have also been mapped in mice, and differences in the relative frequency of the target cell (target size) may be one genetically determined risk factor (recently reviewed by Jawad et al 2007b). For example, QTL that determine the susceptibility to spontaneous pre-B and T lymphomas were both mapped to proximal chromosome 17 (Yamada et al 1994a(Yamada et al , 1994b, and thus implicates the H-2 complex in both the regulation of bone marrow stem and progenitor cell frequencies and a susceptibility to spontaneous lymphoid lymphomas.…”
Section: Discussionmentioning
confidence: 99%